Simulation-Assisted Approach for Determining Wear-Limited Tool Life in the Coining Process - Garcia-Herrera, C; Navarrete-Rosales, A (Springer Science and Business Media Deutschland GmbH, 2020)
Efficiency of coin manufacturing is often limited by the service life of the stamping dies, whose degradation by wear results in decreasing the quality of the produced coin engraving. The aim of this work is to explore the ability of the combined application of experimental characterization and numerical simulation of the material elastoplastic forming response, friction effects, and die material wear rate as a tool to contribute to the coin design in order to ultimately increase the number of coins that can be die forged before the use of a worn die compromises the desired quality of the final product. The following aspects have been particularly addressed in this study. First, the influence of two design parameters related with the quality of the coins, i.e., die displacement and depth of engraving, is quantified determining that the die displacement is the most preponderant since the stamping force needed in this process is higher compared with that obtained by varying the depth of engraving. In addition, it is found that the curvature of the coin relief determines the local stress distribution, in some cases even at the opposite die, resulting in a heterogeneous wear evolution. A complementary wear test reveals that, for the involved range of curvatures, the wear mechanism may shift from dominated by plowing/cutting to dominated by fatigue. It is concluded that the numerical simulation allows considering efficiency of the coining process already at the stage of the aesthetic design of a coin. © 2020, Springer-Verlag London Ltd., part of Springer Nature.
Keywords: Coining process; Modeling; Numerical simulation; Ring compression test; Pin on disc